Study of effects of blood alcohol consumption (BAC) level on drivers physiological behavior and driving performance under simulated environment - Subramaniyam, Murali; Eun Kim, Seoung; Nam Min, Seung; Lee, Heeran; Hee Hong, Seung; Jin Park, Se (International Journal of Engineering and Technology, 2018)
Alcohol consumption impairs driving skills and responsible for a high proportion of traffic accidents. This research examined the effects of blood alcohol consumption (BAC) level on driver’s physiological behavior and driving performance under simulated driving environment. The participants consisted of eight healthy young male drivers with an average of eight years driving experience. The scenario considered was 5 min driving on a highway with different speed limits, crossings, and unexpected event. Results showed that statistically significantly decreased alpha and increased theta power frequency was observed with increased BAC level. Heart rate was statistically significantly elevated with increased BAC level. The accident rate and the over speed rate were significantly higher with higher BAC level. Alcohol intoxication affected drivers’ decision-making ability, vision and integrating visual information ability.